Highly elastic polymer substrates with tunable mechanical properties for stretchable electronic applications. Issue 109 (11th November 2016) - Gandla, Srinivas; Gupta, Harshad; Pininti, Anil Reddy; Tewari, Amit; Gupta, Dipti
Abstract : Stretchable electronic devices have recently gained a lot of attention because of their applications in healthcare and wearable electronics and their other innovative applications. Abstract : Stretchable electronic devices have recently gained a lot of attention because of their applications in healthcare and wearable electronics and their other innovative applications. The approach to make stretchable electronic systems commonly utilizes a soft stretchable matrix embedded with rigid islands such that the softer part undergoes mechanical deformation during stretching while the stiff portion remains unaffected. In this paper, we have worked on developing these soft–stiff systems using a preparation scheme, which is extremely simple; one-step and is capable of fabricating highly stretchable substrates. The stretchable substrate composed of a soft matrix and rigid islands has elastic modulus values of ∼0.04 MPa and ∼2.6 MPa, respectively. The fabrication process involves adding poly(dimethylsiloxane)-poly(ethylene oxide) (PDMS- b -PEO) and benzophenone (BP) to an elastomer poly(dimethylsiloxane) (PDMS) followed by ultra-violet light exposure using a photomask. PDMS- b -PEO reduces the elastic modulus of PDMS, while BP helps the photopatternability. This fabrication strategy enabled the preparation of locally tunable elastic substrates that are reversibly stretchable up to 200% while the softer region stretches up to ∼300%. Further, the metal films coated on rigid islands show no change in conductivity under tensile loading. Finally, we transferred an organic thin film transistor (OTFT) on the stiffer regions of the stretchable substrate and demonstrated that the electrical characteristics of OTFT remain unaffected under various degrees of applied strain.